(untitled) (Journal of Contemporary Philology, 2019)
The present paper explores the quest of Miriam Henderson, the main protagonist in Dorothy Richardson’s thirteen-volume novel Pilgrimage, for religious identity and its connection to music. Pilgrimage has previously been read as a quest narrative by several critics, but the role of music in the pursuit for deconstruction and an ultimate refute of Miriam’s Anglican religious tradition has been neglected. By comparing the religious practices of Anglicanism and Lutheranism during the protagonist’s stay in Germany in the first volume Pointed Roofs, and their relevance to congregational singing, choice of hymns and the sermons, Miriam starts her quest aimed at redefining her religious identity. In this paper we review the stages of Miriam’s religious quest by outlining her path towards revelation and establishing a new relation to God throughout the volumes Backwater, The Tunnel, Deadlock, The Trap, Clear Horizon and March Moonlight.